Effect of Silane Treatment of Aluminum Oxide Nanoparticles on its Antimicrobial Property in Polymethyl Methacrylate Denture Base Resin - Trupti Bangre; Rajlakshmi Banerjee; Priti Jaiswal; Jyoti Sharma; Vijeta Gajbhiye (Journal of International Clinical Dental Research Organization, 2025)
Introduction: Candida albicans is a common causative agent causing denture stomatitis. Recent studies have shown an increase in antimicrobial properties of denture base resin reinforced with nanoparticles after silanization of the particles. Therefore, a study was planned to evaluate and compare the antimicrobial effectiveness of heat-polymerized polymethyl methacrylate denture base material reinforced with nonsilanized and silanized aluminum oxide nanoparticles and without the reinforcement of aluminum oxide nanoparticles against C. albicans. Materials and Methods: A total of 60 specimens were prepared using heat polymerized acrylic resin and grouped into three groups Group C, Group N, and Group S as nonreinforced, aluminum oxide reinforced, and silanized aluminum oxide reinforced, respectively. The samples were then inoculated with microorganisms and cultured for 24 h. The antimicrobial property was evaluated by counting the colonies observed and counted as the number of colony-forming units (CFUs). Results: The mean CFU/ml in group S (1.19 ± 0.12) was statistically significantly less than group C (4.48 ± 0.04) and group N (2.37 ± 0.04) (P < 0.0001). The mean CFU/ml in group S was statistically significantly less than in group N as indicated by P < 0.0001. Furthermore, the mean CFU/ml in group N was statistically significantly less than in group C (P < 0.0001). Conclusion: Dentures fabricated by incorporation of silanized aluminum oxide nanoparticles help in the maintenance and increasing the life of the prosthesis by eliminating organic material harboring microorganisms remaining on the prostheses